Direct Evidence of Symmetry between Bilateral Human Corneas in Biomechanical Properties: A Comparison Study with Fresh Corneal Tissue - Chao Xue; Yaoqi Xiang; Yi Song; Min Shen; Di Wu; Yan Wang (Journal of Ophthalmology)
Purpose. To investigate the difference between the eyes from the same human with respect to the biomechanical properties of fresh corneal tissues and investigate the assumption of similarity of the corneal biomechanical properties between the eyes. Methods. Strip specimens extracted through a small incision lenticule extraction (SMILE) surgery were tested using a uniaxial tensile test. The specimens were extracted vertically. Low-strain tangent modulus (LSTM), high-strain tangent modulus (HSTM), and tensile strength (σb) were the biomechanical parameters used in the comparison of the eyes from the same human. Results. Ninety corneal specimens from 45 persons were included in this study. The LSTM of the left and right eyes were 1.34 ± 0.52 and 1.37 ± 0.46 MPa, while the HSTM were 50.53 ± 7.51 and 49.41 ± 7.01 MPa, respectively. There was no significant difference between the eyes in terms of LSTM, HSTM, andσbP=0.813, 0.335, and 0.605, resp.. The LSTM and HSTM were significantly correlated with the spherical equivalent (SE) (P≤0.01, P=0.001, resp.). Conclusions. The assumption that the corneal biomechanical properties of the eyes from the same human are similar has been confirmed for the first time using fresh human corneal tissue. This finding may be useful in further biomechanical studies.